The Impact of Global Uncertainty on Indonesia's Economic Stability: An Empirical Study for the Period 2020-2025 - Heri Ardian; Adi Putra; Nurdin Nurdin; Sunandar Sunandar (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the impact of global uncertainty on Indonesia's economic stability in the period 2020-2025. Global uncertainty triggered by various external factors such as the global health crisis (covid-19 pandemic), commodity price fluctuations, changes in international trade policies, and geopolitical tensions, can have a significant impact on the economies of developing countries such as Indonesia. This study examines how global uncertainty affects Indonesia's key economic indicators, including economic growth, inflation, the rupiah exchange rate, and foreign investment flows. The method used in this study is econometric analysis with multiple linear regression model, which involves secondary data from various official sources such as Bank Indonesia, Central Bureau of Statistics, and international institutions. The results of this study are expected to provide a clearer picture of the extent to which global uncertainty affects Indonesia's economic stability and what economic policies need to be taken by the government to maintain economic stability in the face of external threats. In addition, the study will also identify sectors of the economy that are more vulnerable to the impact of global uncertainty and provide policy recommendations that can strengthen Indonesia's economic resilience.